Rima, Ritme dan Pesan Moral dalam Syi’ir Huruf “Ba” Karya Umru’ al-Qais (Kajian ‘arudh dan Qawafi): Rhyme, Rhythm and Moral Message in the Syi'ir Letter "Ba" by Umru' al-Qais (Study of 'arudh and Qawafi) - Fauziah Aulia Fatimah; Dedi Supriadi; Maman Abdul Djaliel (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
This study aims to analyze the rhyme, rhythm, and moral message in the qafiyah poem "ba" by Umru' al-Qais through the approach of 'arudh and qawafi sciences. This study is motivated by the importance of understanding the relationship between the sound structure of classical Arabic poems and their meanings. The poem by Umru' al-Qais was chosen because it is one of the most important works in Jahiliyah Arabic literature, with high aesthetic value and rich linguistic and moral elements. The study uses a descriptive qualitative approach, with data sources consisting of poems from the diwan of Umru' al-Qais. The analysis was carried out by examining the bahar pattern, taf'ilah, changes in zihaf, and the qafiyah structure in eight verses of the poem, then connecting them to the moral message in each verse. The results of the study show that the poem consistently uses bahar thawil with various changes in taf'ilah, especially in the form of zihaf qabadh, which affects its rhythm and musicality. The qafiyah structure is dominated by the qafiyah muthlaqah form, with the rawi letter "ba" followed by the washl letter "ya", resulting in a strong harmony of sound. In addition to functioning as aesthetic elements, rhyme and rhythm also play a role in emphasizing the delivery of meaning. The poem's moral messages include individual, social, and religious values, such as honesty about feelings, the importance of loyalty and trust in relationships, and awareness of human limitations in the face of destiny. Thus, this study demonstrates the integration of sound structure and meaning, enriching the study of classical Arabic literature.